2012
DOI: 10.1002/acp.2822
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Skills in the Context of Non‐Suggestive Investigative Interviews: Impact of Structured Interview Protocol and Feedback

Abstract: Two groups of police investigators were trained in the use of the National Institute of Child Health and Human Development (NICHD) interview protocol. After the training, one group (n = 8) received written feedback on each interview they conducted, whereas the other group (n = 11) did not. The objective of the study was, first, to evaluate the effect of NICHD protocol implementation on the types of questions and details provided by children and, second, to evaluate the impact of post-training feedback. Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 53 publications
5
47
0
4
Order By: Relevance
“…We need to understand more fully why interviewers use the strategies they do so we can identify how to promote adhering to best‐practice tenets. Researchers have demonstrated that regular and focused guidance and supervision promote effective interviewing practices , yet the available pool of qualified and experienced supervisors is limited. As a result, we should invest in research examining other ways to access supervision and review practice (e.g., Web‐based supervision, self‐reflective exercises; ).…”
Section: Looking Aheadmentioning
confidence: 99%
“…We need to understand more fully why interviewers use the strategies they do so we can identify how to promote adhering to best‐practice tenets. Researchers have demonstrated that regular and focused guidance and supervision promote effective interviewing practices , yet the available pool of qualified and experienced supervisors is limited. As a result, we should invest in research examining other ways to access supervision and review practice (e.g., Web‐based supervision, self‐reflective exercises; ).…”
Section: Looking Aheadmentioning
confidence: 99%
“…In Quebec, Canada, there are some police departments with only one interviewer, posing a challenge for external feedback: (Cyr, Dion, McDuff, & Trotier-Sylvain, 2012)." -Mireille Cyr, Canada Adopting the NICHD protocol when legal system requirements may pose a challenge All of the experts who have provided commentary on the use of the NICHD protocol throughout this review work in countries where the legal system already encourages high-quality interviewing of child victim/witnesses, or where recent changes have taken place to facilitate the transition to incorporating the Protocol.…”
Section: "Initial Training However Intensive Is Not Enough To Maintmentioning
confidence: 99%
“…The interviewing of child witnesses is no exception (Cyr, Dion, McDuff, & Trotier-Sylvain, 2012;Powell, Fisher, & Hughes-Scholes, 2008). Without feedback, interviewers have little idea about whether their interviewing is good or bad, improving or getting worse.…”
Section: Access To Field Interviews For Evaluation and Feedbackmentioning
confidence: 98%